Satisfacción laboral de los empleados de la Pastelería y Panadería California - Muñoz Caregua, Johana Anabel (2019)
Every institution independently of the activities it performs is made up of different resources, necessary for the development of its business activities, and the fulfillment of the short and long-term objectives, which have been established at the beginning of the constitution of the company, without However, there may be equipment, machinery, or some other material, but undoubtedly human capital is the indispensable element for organizational success, which is why the human talent of an organization must be motivated within its work environment, because it is the right way to get an adequate collective performance.